Ambar's corporate turnaround: from insolvency to expansion - Konoplev, Roman Vadimovich (2021)
In 2013, at the Commercial Court of Vila Nova de Gaia, was being discussed Ambar’s insolvency, after 30 workers had filed a request for insolvency of this Portuguese stationery company. Ambar was extremely indebted, the production had come to a halt, the company had no raw material to work with and its employees had not been paid for several months. Six years later, in 2019, the company was selling to more than 500 clients in 25 countries, exporting 40% of total sales, and planning to invest €10 million to expand its business and to develop a sustainable growth strategy. With the present Case Study, we aim to explore the concept of Corporate Turnaround in a simple and engaging way, with the intention of inviting Master’s students to participate in the Case Resolution, by choosing a real-life example. In order to do so, this project follows the process since the first signs of distress until the insolvency process, and explores the successful recovery of Ambar and the company’s expansion. By providing a detailed analysis of Ambar’s external factors, describing the insolvency procedures in Portugal, offering an analysis of the Corporate Turnaround Process, discussing the implemented measures and other factors that contributed for the recovery, and given the 2020 worldwide pandemic situation - with an increasing amount of company failures and growing unemployment -, this Project presents an additional value for companies in similar conditions and may be used as a helpful guide.